Effects of Evaporative Cooling Air Conditioning on Classroom Pollutants and Thermal Environment - Lu Xiao; Zhenyu Du (SAGE Publishing, 2022)
Indoor particles and carbon dioxide concentration are major indices to evaluate indoor air quality. Based on the two-dimensional filler sieving model of the direct evaporative cooling segment, the porous media model was used for the simulation of the water filler section, the filtering efficiency of particle was simulated by adjusting the water drenching density and airflow velocity in different operating conditions. The three-dimensional classroom model used to change the exhaust outlet position and control the use of air conditioners simulated the indoor thermal environment and the changes in pollutant concentration. The Euler method and Lagrangian method were used to analyze the indoor flow field and particle sieving in the direct evaporation section, respectively. Conclusions show that in the application of evaporative cooling and stratum ventilation air conditioning system in classroom, the position of the exhaust port affects the concentration of carbon dioxide in the student's breathing area. The water filler section can effectively reduce the concentration of particle and carbon dioxide supplied indoors. The filtration efficiency of particle in outdoor air passing through the direct evaporative cooling section based on diffusion, inertial collision, and interception is affected by the combined effect of particle size, onward wind speed, and water spray density. The filtration efficiency of particle increases as the density of the spray water increases. With the increase of head-on wind speed, the filtration efficiency of coarse particulate matter is higher than that of fine particulate matter. The research results help policy makers decide whether to install evaporative cooling air conditioning in schools and determine which exhaust outlet positions are most effective in improving indoor air quality.